Case Series of Adverse Pregnancy Outcomes Associated with Oropouche Virus Infection - Daniele Barbosa de Almeida Medeiros; Juarez Antônio Simões Quaresma; Raimunda do Socorro da Silva Azevedo; Ana Cecilia Ribeiro Cruz; Sandro Patroca da Silva; Arnaldo Jorge Martins Filho; Bruno Tardelli Diniz Nunes; Lucas Rafael Santana Pinheiro; Jorge Rodrigues de Sousa; Jannifer Oliveira Chiang; Lívia Carício Martins; Consuelo Silva Oliveira; et al. (Viruses)
The Oropouche virus (OROV) is an arbovirus (Peribunyaviridae: Orthobunyavirus) that traditionally causes febrile outbreaks in Latin America’s Amazon region. Previously, OROV was not associated with severe pregnancy outcomes. During the 2022–2024 outbreak in Brazil, OROV expanded geographically, revealing links to adverse pregnancy outcomes. This study describes six cases with varied fetal outcomes, including miscarriage, antepartum, intrauterine fetal demise (IFD), and normal development, correlating with maternal symptoms but not symptom severity. Vertical transmission was confirmed by detecting OROV through RT-qPCR, ELISA, and immunohistochemistry in fetal tissues. Genome sequencing from an IFD case identified a novel reassortment pattern reported in the 2022–2024 outbreak. Severe encephalomalacia, meningoencephalitis, vascular compromise, and multi-organ damage were evident, underscoring the significant risk OROV poses to fetal development and emphasizing the need for further investigation.